2023
DOI: 10.3390/coatings13020302
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of the Water Damage Resistance of Tuff Asphalt Mixture Modified with Additives

Abstract: To improve the water damage resistance performance of a tuff asphalt mixture, a tuff mixture with cement and a liquid anti-stripping agent was used as the research object, and limestone and tuff mixtures without additives were selected as contrast samples. Through an improved boiling test and a water stability test before and after aging, the modification effect of the tuff mixture with additives of different types and contents on water damage resistance was evaluated to obtain the appropriate type and content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…SBS-modified asphalt was selected as the binder of the asphalt mixture, which came from the Zhejiang Transportation Resources Investment Co., Ltd., Hangzhou, China [15]. The technical indexes of SBS-modified asphalt binder were tested by referring to the test methods of the JTG E20-2011 specifications [21]; they are provided in Table 1, indicating that the SBS-modified asphalt binder conformed to the requirements of the JTG F40-2004 specifications [22,23].…”
Section: Asphalt Bindermentioning
confidence: 99%
See 2 more Smart Citations
“…SBS-modified asphalt was selected as the binder of the asphalt mixture, which came from the Zhejiang Transportation Resources Investment Co., Ltd., Hangzhou, China [15]. The technical indexes of SBS-modified asphalt binder were tested by referring to the test methods of the JTG E20-2011 specifications [21]; they are provided in Table 1, indicating that the SBS-modified asphalt binder conformed to the requirements of the JTG F40-2004 specifications [22,23].…”
Section: Asphalt Bindermentioning
confidence: 99%
“…For instance, Goual et al [14] investigated the strength of tuff-limestone sand mixtures with different cement contents through laboratory tests, and the results indicated the possibility of the development on asphalt pavement materials containing tuff in Algeria. Zhang et al [15] evaluated the performance of a tuff asphalt mixture after adding cement and a liquid antistripping agent through laboratory tests, and the results indicated that the addition of admixtures could improve the adhesion property and water stability of the tuff mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze-thaw cycles, water action, and traffic are the main distresses of asphalt pavements in seasonal frozen regions [10,11]. These factors can lead to the deterioration of the pavement, causing cracks, rutting, and other forms of damage.…”
Section: Introductionmentioning
confidence: 99%
“…This is a new form of technology used in the construction and paving of asphalt pavement. A second example of asphalt pavement is described in the article entitled "Laboratory investigation of the water damage resistance of tuff asphalt mixture modified with additives" [2]. In this case, to improve the water damage resistance of a tuff asphalt mixture, cement and liquid anti-stripping agents were added to the aforementioned tuff asphalt mixture, and limestone and tuff mixtures without additives were used as comparison samples.…”
mentioning
confidence: 99%